The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1136/emermed-2019-209307
|View full text |Cite
|
Sign up to set email alerts
|

Risk of significant traumatic brain injury in adults with minor head injury taking direct oral anticoagulants: a cohort study and updated meta-analysis

Abstract: BackgroundPatients taking direct oral anticoagulants (DOACs) commonly undergo CT head imaging after minor head injury, regardless of symptoms or signs. However, the risk of intracranial haemorrhage (ICH) in such patients is unclear, and further research has been recommended by the UK National Institute for Health and Care Excellence head injury guideline group.MethodsAn observational cohort study was performed in the UK South Yorkshire major trauma centre between 26 June and 3 September 2018. Adult patients ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
30
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 32 publications
6
30
2
Order By: Relevance
“…Hrr in the brain parenchyma following TBI could be a space-occupied mass and thus could induce the compressive pressure to local tissue followed by a reduction of blood flow and intracranial pressure (ICP) elevation. In addition, recent studies have shown that anticoagulant therapy, including warfarin, worsens the symptoms rapidly in patients with TBI due to side effects such as massive Hrr ( 7 ). Therefore, therapeutic management of Hrr or hematomas might be a key point in the treatment of TBI, which is a common procedure in clinics.…”
Section: Introductionmentioning
confidence: 99%
“…Hrr in the brain parenchyma following TBI could be a space-occupied mass and thus could induce the compressive pressure to local tissue followed by a reduction of blood flow and intracranial pressure (ICP) elevation. In addition, recent studies have shown that anticoagulant therapy, including warfarin, worsens the symptoms rapidly in patients with TBI due to side effects such as massive Hrr ( 7 ). Therefore, therapeutic management of Hrr or hematomas might be a key point in the treatment of TBI, which is a common procedure in clinics.…”
Section: Introductionmentioning
confidence: 99%
“…There is sparse and conflicting evidence directing the outcomes and management of head injury in patients anticoagulated with DOAC. [ 2 ] DOAC have become the new standard anticoagulants replacing the Vitamin K antagonists (VKA) in clinical practice worldwide. Research on the outcomes of such patients of traumatic brain injury (TBI) becomes important to guide the management practices.…”
mentioning
confidence: 99%
“…[ 3 ] The guidelines are based on the systematic reviews of the available literature, but we need to take the results of these systematic reviews with a pinch of salt because the studies they included were very heterogeneous in the nature of their study designs and inclusion and exclusion criteria. [ 2 ]…”
mentioning
confidence: 99%
See 2 more Smart Citations